2015
DOI: 10.4278/ajhp.130403-quan-148
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Neighborhood Income and Access to Quality Physical Activity Resources to Physical Activity in Ethnic Minority Women over Time

Abstract: Purpose To create and test an index to indicate both availability and quality of physical activity (PA) resources (PARs), to examine associations between access to quality PARs and changes in PA, and to determine whether this association differed in lower- and higher-income neighborhoods. Design Longitudinal, 6-month intervention. Setting. Houston and Austin, Texas. Subjects African-American and Hispanic or Latina women. Measures Women (N = 410) completed a questionnaire and accelerometry to measure PA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 31 publications
1
32
1
3
Order By: Relevance
“…It contributes to an emerging literature on disparities in specific park characteristics that associate with physical activity and weight status. 27,28,39 Several differences between the number, presence or absence, conditions, and cleanliness of park features were found. For example, more trash cans were present in parks in minority areas, but sitting and resting amenities were less clean than those in non-minority area parks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It contributes to an emerging literature on disparities in specific park characteristics that associate with physical activity and weight status. 27,28,39 Several differences between the number, presence or absence, conditions, and cleanliness of park features were found. For example, more trash cans were present in parks in minority areas, but sitting and resting amenities were less clean than those in non-minority area parks.…”
Section: Discussionmentioning
confidence: 99%
“…38 Higher quality physical activity resources within neighborhoods have been found to translate to higher levels of physical activity among minority women. 39 Studies have documented significantly greater numbers of quality issues 40 and fewer amenities 29 in parks located in low-income areas. Vaughan and colleagues observed fewer playgrounds and lower quality in parks in low-income census tracts and more basketball courts and fewer trails in high minority areas.…”
Section: Introductionmentioning
confidence: 99%
“…However, Vieira et al 12 found significant positive association between the level of social development of a neighborhood and quality of parks for physical activity in Rio de Janeiro, Brazil. This can partially explain the association found between living in low income areas and level of social development, with lower levels of physical activity [13][14][15] .…”
mentioning
confidence: 91%
“…• Quality of parks for physical activity The Physical Activity Resource Assessment (PARA) instrument was developed to systematically identify and describe the type, features, amenities, and quality of physical activity resources in urban neighborhoods 14,28 . This instrument was translated and adapted to the Latin American context 29 and has been used recently in Latin America regions 12,29 .…”
Section: Dependent Variablesmentioning
confidence: 99%
See 1 more Smart Citation